2022
DOI: 10.1002/ar.25131
|View full text |Cite
|
Sign up to set email alerts
|

Comparative postcranial osteohistology and bone histovariability of aquatic and terrestrial turtles: the case of the South American Phrynops hilarii, Hydromedusa tectifera (Pleurodira, Chelidae), and Chelonoidis chilensis (Cryptodira, Testudinidae)

Abstract: This article presents a detailed comparative analysis of the bone microstructure of three extant species of South American turtles. The main histological characteristics of postcranial bones are identified, as well as the intraskeletal, ontogenetic and interspecific variation between aquatic and terrestrial species. For this purpose, thin sections of postcranial bones (seventh cervical vertebra, coracoid, scapula, humerus, radius, ulna, ischium, ilium, pubis, femur, tibia, and fibula) of juvenile and adult spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…mississippiensis, Chabreck & Joanen, 1979;Horner et al, 2001;Padian et al, 2004;Rainwater et al, 2021;Reid, 1997aReid, , 1997bde Ricqlès et al, 2003;Roberts et al, 1988;Tumarkin-Deratzian, 2007;Werning, 2013;Woodward et al, 2014; Crocodylus sp., Enlow, 1969 Chinsamy, 1991). Some of these earlier studies also reported a concentric arrangement of the LVCs in other reptiles (e.g., Botha & Botha, 2019;Navarro et al, 2023;Pellegrini et al, 2021;Pereyra, 2022;Werning, 2013). In C. latirostris, we also observed radially organized vascular canals in specific bones (e.g., scapula of MLPR-6822 and tibia of MLPR-6809).…”
Section: Discussionmentioning
confidence: 89%
“…mississippiensis, Chabreck & Joanen, 1979;Horner et al, 2001;Padian et al, 2004;Rainwater et al, 2021;Reid, 1997aReid, , 1997bde Ricqlès et al, 2003;Roberts et al, 1988;Tumarkin-Deratzian, 2007;Werning, 2013;Woodward et al, 2014; Crocodylus sp., Enlow, 1969 Chinsamy, 1991). Some of these earlier studies also reported a concentric arrangement of the LVCs in other reptiles (e.g., Botha & Botha, 2019;Navarro et al, 2023;Pellegrini et al, 2021;Pereyra, 2022;Werning, 2013). In C. latirostris, we also observed radially organized vascular canals in specific bones (e.g., scapula of MLPR-6822 and tibia of MLPR-6809).…”
Section: Discussionmentioning
confidence: 89%
“…The authors digitally dissected 3D models from micro‐CT scans of 70 extant species and observed 51 morphological characters, some with high systematic value. Comparative osteohistological anatomy of aquatic and terrestrial turtles is provided by Pereyra (2023). The bone histology described by Pereyra (2023) reveals that there is intraskeletal variation of the microanatomical and microstructural organization in the analyzed turtles providing valuable data about their paleobiology.…”
Section: Contributions To the Turtle Evolution Symposium 2021mentioning
confidence: 99%
“…Comparative osteohistological anatomy of aquatic and terrestrial turtles is provided by Pereyra (2023). The bone histology described by Pereyra (2023) reveals that there is intraskeletal variation of the microanatomical and microstructural organization in the analyzed turtles providing valuable data about their paleobiology. Krahl and Werneburg (2023) use anatomical network analyses to explore the flipper in marine turtles and other amniotes secondarily adapted to the marine environment.…”
Section: Contributions To the Turtle Evolution Symposium 2021mentioning
confidence: 99%
“…Some appear randomly or stacked together within the compacta, and special growth marks are deposited at the time of hatching in reptiles [39], and at the time of birth in mammals (neonatal line) (sensu [92]). Indeed, often certain bones in a single skeleton, such as the stylopodium (humerus, femur) and zeugopodium (fibula, tibia, radius andulna), retain better growth mark record than the bones of cervical vertebrae, and in some cases, variation is noticed at different ontogenetic levels [62]. However, Bhat et al [48] reported that the tibia retains better growth mark record in angulate tortoises.…”
Section: Perimeter Measurements Of Lines Of Arrested Growthmentioning
confidence: 99%
“…[52]). Moreover, although histological studies on chelonian limb bones and/or shell bones have been used to determine skeletochronology and reconstruct growth rates of the testudines [48,49,[53][54][55][56][57][58][59][60][61][62], histological data from a single species, involving both modern and fossilized individuals is non-existent. Here, we fill this gap by investigating the bone histology of Chersina angulata from the Miocene to present, to assess whether their growth dynamics and life-history patterns changed over the past 5 million years.…”
Section: Introductionmentioning
confidence: 99%